Le pèlerinage des indiens Tojolabal (Chiapas-Mexique) à San Mateo Ixtatan (Guatemala), rite agricole et relations interethniques - Carine Chavarochette (Cahiers des Amériques Latines)
This article analyzes a transborder pilgrimage, annually carried out by Tojolabal Maya populations of Mexico to Guatemala. Beyond the veneration of a god of the rain and an agricultural rite necessary to the survival of these populations of farmers, this group built or rather rebuilt its identity on the basis of migration. These pilgrims join temporarily another group of metis farmers before returning in contact with another Guatemalan Maya group, the Chuj. The course carried out and the veneration symbolic system of the territory make it possible for Tojolabal to highlight their Guatemalan mythical origins while affirming their current frontier identity, «chiapaneca» and to a lesser extent Mexican.